KINETIC STUDY AND PRODUCT CHARACTERIZATION OF SKARN TYPE PRIMARY TIN ORE GRINDING USING VARIATION OF BALL FILLING, FEED GRINDING BALL RATIO, AND MILL ROTATION SPEED - Bagus Arif Indradi Edija, Raden
Tin is one of metal element that present in huge amount in Indonesia, especially in Kepulauan Bangka Belitung. High reserves are also followed by tin metal production in Indonesia, which is the second highest in the world. One of the companies that is engaged in producing tin is PT. Timah Tbk which had done mining in Batubesi area, Belitung. Ore deposits in Batubesi area are deposits of oxide clay, greisen, and skarn type ore. Among the types of ore, skarn type ore has the characteristics of hard ore, so that the comminution process is needed. In this experiment, grinding was conducted to find out influence of ball filling, feed ratio with ball mill, and mill rotation speed variations toward the size of the primary tin ore grinding products, grinding kinetics, and mineragraphy observation. Ore preparation is done by doing crushing using roll crusher to produce a size of 2370 ?m which will be used as grinding feed. The grinding process is done for 150 minute with ball filling variable (20% volume, 30% volume, 40% volume, and 50% volume), feed ratio with ball mill (1:10; 1:8; 1:6; and 1:4), and mill rotation speed (50% Nc, 60% Nc, 70% Nc, and 80% Nc) also sieve analysis is done at each interval grinding time. The result will be used for linear regression model analysis In this study, kinetics study of skarn type primary tin ore with variations of ball filling volume percentage shows that the highest value of initial rate of formation for all ball filling volume variations achieved at a particle size of 250 ?m where the highest initial rate of formation occurs in 50% mill volume. Variations of feed ratio with ball mill shows that the highest value of initial rate of formation for 1:10, 1:8, and 1:6 achieved at a particle size of 250 ?m and for 1:4 ratio at a particle size of 297 ?m where the highest initial rate of formation occurs in 1:10 feed ratio with ball mill. Variations of mill rotation speed shows that the highest value of initial rate of formation for all mill rotation speed variations at a particle size of 250 ?m where the highest initial rate of formation occurs in 80% Nc mill rotation speed. In this research produced two regression model that can predict P80 value based on the grinding variables in this study. In mineragrafi observation, well separated particles start at particle size -105 +63 ?m.